Does God Think the Same Way We Do? On the Logical Apophatism of Michał Heller - Grygiel, Wojciech (Verbum Vitae, 2023)
Apophatic theology is an approach in theology that emphasizes the limitation of human language and concepts in describing the nature of the Divine. Rooted in ancient religious traditions, apophatic theology has gained attention in contemporary discourse for its potential convergence with the scientific method. This paper expands on a novel application of this approach in which the formal methods of science such as logic and mathematics are engaged to inquire into how God thinks and to what degree the modes of human reasoning can be projected on the nature of the Divine mind. This application has been proposed by Michał Heller and is referred to as the logical apophatism. In the course of the analysis carried out in this paper more in-depth understanding of the logical apophatism has been obtained by contrasting it with classical approaches to negative theology such as the Triplex Via and supplementing with recent advances within the cognitive sciences. It is concluded that Heller’s use of the apophatic approach is manifestly non-standard and its novelty consists in the shift of emphasis from the negative character of the language of theology to the logic of the Divine mind and the logic that underpins the workings of the Universe.